2004
DOI: 10.1002/bip.20023
|View full text |Cite
|
Sign up to set email alerts
|

Water‐mediated contacts in thetrp‐repressor operator complex recognition process

Abstract: Water-mediated contacts are known as an important recognition tool in trp-repressor operator systems. One of these contacts involves two conserved base pairs (G(6).C(-6) and A(5). T(-5)) and three amino acids (Lys 72, Ile 79, and Ala 80). To investigate the nature of these contacts, we analyzed the X-ray structure (PDB code: 1TRO) of the trp-repressor operator complex by means of molecular dynamics simulations. This X-ray structure contains two dimers that exhibit structural differences. From these two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Some water-mediated interactions are energetically quite favorable and can be trapped in the crystal structure. This result is consistent with previous observations of solvent present on protein-DNA interfaces (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Resultssupporting
confidence: 93%
“…Some water-mediated interactions are energetically quite favorable and can be trapped in the crystal structure. This result is consistent with previous observations of solvent present on protein-DNA interfaces (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Resultssupporting
confidence: 93%
“…(There was no significant difference in the stripped and unstripped starting structures.) Simulations of the Trp repressor-operator complex (Wibowo et al, 2004) also showed that water molecules with multi-ns residence times participate in contacts that are critical to complex stability as deduced from site-directed mutagenesis studies (Joachimiak et al, 1994).…”
Section: Crystal Structure and Molecular Dynamics Simulations Of The mentioning
confidence: 96%
“…The BI or BII DNA backbone conformation is characterized by the difference in torsion angles ϵ and ζ [(ϵ − ζ) is negative in BI and positive in BII]. BII is a conformational sub‐state of B‐DNA which has been observed to play a key role in DNA‐protein recognition,17 and the BI ↔ BII transition has been investigated in several studies 18–25…”
Section: Introductionmentioning
confidence: 99%